2018
DOI: 10.1101/378190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobility in Osteogenesis Imperfecta: A Multicenter North American Study

Abstract: Background: Osteogenesis imperfecta (OI) is a genetic connective tissue disorder characterized by increased bone fragility and recurrent fractures. The phenotypic severity of OI has a significant influence on the ability to walk but little is known about the ambulatory characteristics, strength, or functional abilities in individuals with OI, especially in the more severe forms. To advance clinical research in OI, the Linked Clinical Research Centers, network of clinical centers in North America with significa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In agreement with Kruger et al 19 , we found that the OI type was associated with mobility outcomes in the rodded group. Additionally, within the rodded group, a height deficit was associated with reduced mobility outcomes, agreeing with the literature in which height has been related to condition severity 19 , 21 , 22 . Although the use of BMI in populations with short stature is controversial because it may overestimate the proportion of obesity 24 , 37 , many studies found a high prevalence of elevated BMI, especially in individuals with OI Type III 33 , 38 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with Kruger et al 19 , we found that the OI type was associated with mobility outcomes in the rodded group. Additionally, within the rodded group, a height deficit was associated with reduced mobility outcomes, agreeing with the literature in which height has been related to condition severity 19 , 21 , 22 . Although the use of BMI in populations with short stature is controversial because it may overestimate the proportion of obesity 24 , 37 , many studies found a high prevalence of elevated BMI, especially in individuals with OI Type III 33 , 38 .…”
Section: Discussionsupporting
confidence: 93%
“…Functional outcomes and quality of life have been reported to be related to condition severity 19 , 34 - 36 . In agreement with Kruger et al 19 , we found that the OI type was associated with mobility outcomes in the rodded group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations